Investigation of Methylglyoxal, soluble Receptor for Advanced Glycation End-products, and Malondialdehyde in Type 2 Diabetes Mellitus with and Without Cardiovascular Risk Factors - Weaam F. Hussien; Estabraq A. R. Al-Wasiti; Mahood. Sh. Khudair; Hayder A. AL-Aubaidy (Diyala Journal of Medicine, 2025)
Background: Type 2 diabetes mellitus is a chronic metabolic illness that significantly increases the probability of cardiovascular disorders among individuals with type 2 diabetes. Oxidative stress represents a central pathophysiological connection between type 2 diabetes mellitus and cardiovascular complications. Hyperglycemia in type 2 diabetes mellitus elevates oxidative stress through multiple pathways, including the production of advanced glycation end products and methylglyoxal, which interact with their receptor advanced glycation end product (sRAGE). These processes enhance the generation of reactive oxygen species, which leads to lipid peroxidation with malondialdehyde serving as a biomarker. Objectives: To investigate the levels of methylglyoxal, sRAGEs, and malondialdehyde in type 2 diabetes patients with and without cardiovascular risk factors. Patients and Methods: The cross-sectional study involved eighty patients with type 2 diabetes diagnosed with and without cardiovascular risk factors. The study used high-performance liquid chromatography (HPLC) to measure serum methylglyoxal and an ELISA kit (Sun Long Biotech, China) to measure serum sRAGE. Malondialdehyde levels were assessed by spectrophotometry. Moreover, measured parameters included FBS, HbA1c, CRP, and lipid profile by the Cobas system using a kit from Roche, Germany. Results: Type 2 diabetes patients with cardiovascular risk factors had significantly higher serum methylglyoxal, sRAGE, and malondialdehyde compared to those without CV risk factors. Furthermore, fasting blood glucose, HbA1c, lipid profile, and CRP are higher in diabetes with CV risk factors compared to those without. Conclusion: The patients with type 2 diabetes and cardiovascular risk factors showed an increase in methylglyoxal, sRAGE, and Malondialdehyde, which are considered useful biomarkers for the indication of T2DM with cardiovascular risk. Keywords: Methylglyoxal, sRAGE, Cardiovascular risk.